Factors influencing the readiness to adopt electric vehicles: A study on Pulau Langkawi as a potential low-carbon island - Nooraini, Ismail (2022)
The government of Malaysia intends to transform Langkawi into Malaysia’s first low-carbon island by 2030 should to be proud of. However, every minute of the amounts of global greenhouse gas emissions and energy use can have an impact on a low-carbon island all around the world. By introducing electric transportation through the use of electric vehicles has an excellent potential to reduce global warming and increase air quality on a low-carbon island worldwide. Nevertheless, there is currently no research on the adoption of EVs for a low-carbon island that focuses on Malaysia. By using qualitative interviews with expert panels, this study attempts to evaluate the key factors impacting the adoption of EVs on the low-carbon island of Langkawi, Malaysia. Government, Advertising and Marketing, Consumers, Infrastructure, and Technology are the five factors highlighted through this study. By integrating the Theory of Change (ToC) to the low carbon readiness concept, the factors are ranked and prioritised using a quantitative AHP method. The result shown that Government is first ranked in importance factor, followed by Consumers, Advertising and Marketing, Technology, and Infrastructure. For the readiness progress, experts determined that the level of readiness by the Government is 35%, Infrastructure is 30%, Consumers is 12.5%, Advertising and Marketing, and the Technology factors are 10%. This priority and readiness progress are intended to benefit policymakers by demonstrating that the elements are sequential or not at the same level, and policymakers' actions can be preceded first by the higher factors indicated. Finally, this research resulted in the development of an EVs adoption readiness evaluation model for low carbon island, Langkawi.